Improving Internal Medicine Resident Comfort With Shoulder and Knee Joint Injections Using an Injection Workshop - Michael K. Seifert; Christina T. Holt; Amy Haskins; William Dexter (Association of American Medical Colleges, 2020)
Introduction Joint injections can be effective treatments for musculoskeletal issues. We examined whether a brief teaching session delivered to residents and faculty would significantly improve resident confidence in performing shoulder and knee joint injections. Methods We implemented a 90-minute workshop instructed by two sports medicine providers. The objectives and content of the workshop included the topics of indications and contraindications, risks and benefits, supplies and setup, and injection techniques, all assessed on 5-point Likert scales. The workshop included a lecture, followed by residents practicing injections on simulation models and identifying key bony landmarks. Outpatient clinic faculty were given the same lecture and practiced on models. The postworkshop questionnaire was administered to the residents 4 months later. Results Eighteen residents participated. Mean confidence for performing knee injections increased from 2.2 to 3.8 immediately postlecture (p = .006). Shoulder injection confidence increased from 1.6 to 3.8 immediately postlecture (p = .0002). Confidence in knowledge of the risks and benefits, supplies needed, and indications increased similarly. Four months postworkshop, confidence levels were sustained above pretesting levels for all areas studied. Faculty members appreciated their workshop since they had not often performed injections. Discussion This brief workshop-style teaching session can provide meaningful, durable improvements in a trainee's confidence regarding performing shoulder or knee joint injections. The session requires few resources and fits into regular didactic sessions. Further development of this model could increase clinical performance and practice confidence and make these procedures more widely accessible to patients.